DEVELOPING MOLLUCAN CONTENT LISTENING MATERIALS FOR STUDENTS SMA ADVENT GRADE XI - Marcy Ferdinandus & Queen Stella Lelong (JURNAL TAHURI, 2019)
The purpose of this research is to develop Mollucan content material for students at Grade XI SMA Advent in Ambon through Research and development design. In collecting the data, the researchers used theoretical try-out, main field try-out and operational field tryout. The results of research showed that the materials were effective for teaching listening to improve students’ ability through introducing Mollucan wisdom for students. The results of theoretical try-out is a score 78% which can be categorized as good. The result of main field try-out showed that the students felt confidence in working on exercise and enjoy them. The result of operational field try-out (testing) showed that from 20 students the average score is 87, which can be categorized as excellent